Pola Komunikasi dalam Pembentukan Karakter Anak di Panti Asuhan Griya Yatim dan Dhuafa Bukittinggi - Lastri Lastri; Elviana Elviana; Erni Erni (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research explores communication patterns in character building for children at the Griya Yatim and Dhuafa Orphanage in Bukittinggi. Through a qualitative approach, this research explores the dominant type of communication, interactions between caregivers and children, as well as supporting and inhibiting factors for character formation in the context of communication. Findings show that instructive and affectionate communication, supported by local cultural values, plays a central role in shaping children's character. Positive interactions and community involvement provide positive impacts, while challenges such as limited resources and contextual changes are overcome through adaptation efforts. The implications of this research are related to the development of training programs in orphanages to strengthen the quality of communication and support the process of children's character formation.